The fate of ten - Lore, Pittacus (New York : Harper, 2015)
For years the Garde have fought the Mogadorians in secret, but now the invasion has begun. If the Garde can't find a way to stop the Mogs, humanity will suffer the same fate as the Lorien: annihilation. When the Elders sent the Garde to Earth, they had a plan -- one which the Garde are finally starting to understand. A group of the Garde traveled to an ancient pyramid in Mexico where they awoke a power that had been hidden for generations. Now this power can save the world or destroy it. It will all depend on who wields it
Keywords: Extraterrestrial beings -- Fiction; Science fiction